The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1097/cmr.0b013e32833906b6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of microphthalmia-associated transcription factor and tyrosinase as markers for circulating tumor cells detection in patients with melanoma

Abstract: The aim of this study was to analyze microphthalmia-associated transcription factor (MITF) as a marker for the detection of circulating melanoma cells, determine its prognostic value in melanoma patients, and compare it with tyrosinase. Blood samples from 201 melanoma patients in all stages of the disease and 40 healthy volunteers were analyzed. RNA was isolated from mononuclear cell fraction of the blood and assayed by reverse transcription-PCR for the expression of MITF and tyrosinase. All samples from healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
0
16
0
7
Order By: Relevance
“…Its detection after treatment is, in fact, a significant independent prognostic indicator for the patients' survival [25]. When it was assayed by RT-PCR along with TYR and MITF transcripts, an increase in the detection rate of CMCs, from 25% to 38% for stages III and IV, respectively, was found [26].…”
Section: Discussionmentioning
confidence: 97%
“…Its detection after treatment is, in fact, a significant independent prognostic indicator for the patients' survival [25]. When it was assayed by RT-PCR along with TYR and MITF transcripts, an increase in the detection rate of CMCs, from 25% to 38% for stages III and IV, respectively, was found [26].…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, several studies have shown the detection of CMC may represent a biomarker that can identify metastatic disease spread. [8, 9, 11, 13, 16–18, 21, 2426, 4043] Polymerase chain reaction (PCR)-based techniques have been used to monitor CMCs for treatment response in metastatic melanoma patients receiving chemotherapy and biochemotherapy. [12, 14, 15, 20, 22, 23] However, the reproducibility of PCR-based detection methods is low,[44, 45] which hinders their reliability and implementation in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Because MCAM promotes progression, it is associated with a more aggressive phenotype and more advanced disease. Alternatively, CMC can be purified by negative selection by lymphocyte depletion with [55,57,71] anti-CD45 antibody [66]. This approach is independent of malignant cell characteristics and appears to have better recovery versus positive selection methods [48].…”
Section: Methods For Circulating Melanoma Cell Enrichment and Detectionmentioning
confidence: 98%
“…To increase CMC detection rate, tyrosinase mRNA has been combined with other mRNA targets [84]. These include melanoma antigen recognized by T-cells (Melan-A/MART-1) [36], microphthalmia-associated transcription factor (MITF) [55], gp100, MAGE-3 [61], and p97 (melanotransferrin) ( Table 2).…”
Section: Target Genes In Ctc Detectionmentioning
confidence: 99%